Mitigating phosphorus loading from Nonpoint Source (NPS) pollution in Sampaloc Lake, San Pablo City through landscape planning approach - Selma, Adrielle L.; Nappy L. Navarra (Quezon City College of Architecture, University of the Philippines Diliman, 2025)
Cultural eutrophication, a rapid nutrient enrichment of water bodies due to pollution from human activities, is an urgent problem for many small lakes because of their lower dilution capability compared to larger water bodies. While increased nutrient levels in lakes result in an increase in biological productivity, excessive nutrients can destabilize the ecosystem and lead to harmful algal blooms, oxygen depletion, fish kills, and water quality decline. Sampaloc Lake, one of San Pablo City’s seven small crater lakes, exemplify this issue as it faces multiple stressors from aquaculture, tourism, and urbanization. The problem, however, is that input from these sources remains difficult to track and mitigate due to their nonpoint and expansive characteristics. To address these challenges, landscape-based interventions for mitigating nutrient inputs must be spatially located in critical nutrient pathways. This study explored the use of hydrologic simulations in identifying phosphorus nutrient sources and pathways using the Soil and Water Assessment Tool (SWAT+) to inform landscape planning in Sampaloc Lake’s catchment area. The study found that the majority of phosphorus loading in Sampaloc Lake came from aquaculture practices. This was used as a basis to create and develop planning scenarios for the mitigation of cultural eutrophication and its impacts in the lake’s catchment area.
Include appendices
Thesis (Bachelor of Landscape Architecture) -- University of the Philippines Diliman
Keywords: Nonpoint source pollution -- San Pablo City; Aquaculture -- San Pablo City; Lakes -- San Pablo City